2013
DOI: 10.1097/aln.0000000000000020
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Limits Microglial Activation after Experimental Brain Trauma through Inhibition of Nicotinamide Adenine Dinucleotide Phosphate Oxidase

Abstract: The neuroprotective effects of propofol after TBI appear to be mediated, in part, through the inhibition of NADPH oxidase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 83 publications
2
57
0
Order By: Relevance
“…We next used the object exploration and discrimination trials of NOR task to assess recognition memory function 13,18,22 and found that repeated mTBI resulted in significant cognitive impairments when compared with sham rats (Po0.01) and single mTBI rats (Po0.05, Figure 3D). Rats with a single mTBI had a significantly impaired discrimination index compared with sham rats (Po0.05).…”
Section: Repeated Mild Traumatic Brain Injury Caused Impairments In Lmentioning
confidence: 99%
See 3 more Smart Citations
“…We next used the object exploration and discrimination trials of NOR task to assess recognition memory function 13,18,22 and found that repeated mTBI resulted in significant cognitive impairments when compared with sham rats (Po0.01) and single mTBI rats (Po0.05, Figure 3D). Rats with a single mTBI had a significantly impaired discrimination index compared with sham rats (Po0.05).…”
Section: Repeated Mild Traumatic Brain Injury Caused Impairments In Lmentioning
confidence: 99%
“…The estimated number of surviving neurons in each field was divided by the volume of the region of interest to obtain the cellular density expressed in counts/mm 3 . For stereological assessment of microglial activation, sections were stained and processed as described previously; 13,18 briefly, 60-mm sections were stained with Iba-1 (1:1,000; #019-19741 Wako Chemicals, Richmond, VA, USA) overnight, incubated with biotinylated anti-rabbit immunoglobulin G antibody (Vector Laboratories, Burlingame, CA, USA) for 2 hours. Sections processed with avidin-biotin-horseradish peroxidase for 1 hour (Vectastain elite ABC kit, Vector Laboratories), and then reacted with 3,30-diaminobenzidine (Vector Laboratories) for color development.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive literature search provides a spectrum of contradicting outcomes in the context of motor function relative to cortical injury in the rat LFP model. Selected LFP studies have shown a correlation between a reduction in cortical lesion volume and motor function improvement (Luo et al, 2013;Otani et al, 2007). In contrast, other studies have shown improved motor behavior with no decrease in cortical lesion volume (Lippert-Gruener et al, 2007).…”
Section: Discussionmentioning
confidence: 99%